Aplikasi Edible Film Antimikroba Sebagai Kemasan Ramah Lingkungan Dalam Meningkatkan Kualitas Dan Daya Terima Bakso Ikan Tenggiri - Nurhayati; Afriani; Agussalim (Jurnal Pembangunan Berkelanjutan, 2021)
Food in general is perishable foods, because the water content contained in it as the main factor causing food damage itself. The need for food packaging that is safe or edible, and does not pollute the environment is the reason in the application of edible antimicrobial film is expected to improve the food safety of mackerel meatballs during storage. This research includes pure research (Experiments) in the Laboratory. The population in this study is fish meatballs made / produced. This study used a complete randomized design factorial. The first factor is the length of storage (0, 12, 24, 36, 48, 60, and 72 hours) while the second factor is the type of packaging (edible film and polyethylene plastic). The treatment in this study is the result of a combination between the first and second factors. The results showed that the use of packaging type and storage length (edible film and plastic polyethylene) had a real effect on the degree of acidity and binding power of water, but had no effect on overall acceptance. Packaging edible antimicrobial film is a packaging that can inhibit the decay process, especially in fish meatballs mackerel up to 72 hours of storage at room temperature.